A Snapshot of Functional Genetic Studies in Medicago truncatula - Kang, Yun; Li, Minguye; Sinharoy, Senjuti; Verdier, Jerome (Frontiers in Plant Science, 2016)
In the current context of food security, increase of plant protein production in a sustainable manner represents one of the major challenges of agronomic research, which could be partially resolved by increased cultivation of legume crops. Medicago truncatula is now a well-established model for legume genomic and genetic studies. With the establishment of genomics tools and mutant populations in M. truncatula, it has become an important resource to answer some of the basic biological questions related to plant development and stress tolerance. This review has an objective to overview a decade of genetic studies in this model plant from generation of mutant populations to nowadays. To date, the three biological fields, which have been extensively studied in M. truncatula, are the symbiotic nitrogen fixation, the seed development, and the abiotic stress tolerance, due to their significant agronomic impacts. In this review, we summarize functional genetic studies related to these three major biological fields. We integrated analyses of a nearly exhaustive list of genes into their biological contexts in order to provide an overview of the forefront research advances in this important legume model plant.